TAZ promotes osteogenic differentiation of mesenchymal stem cells line C3H10T1/2, murine multi-lineage cells lines C2C12, and MEFs induced by BMP9 - Huang, Huakun; Lu, Qiuping; Ye, Caihong; Wei, Mengqi; Yang, Chunmei; Zhang, Lulu; Huang, Yanran; Luo, Xiaoji; Luo, Jinyong (Cell death discovery, 2022)
Bone morphogenetic protein 9 (BMP9), also named as growth differentiation factor 2 (GDF-2), is the strongest cytokine that promotes osteogenic differentiation in the BMP family, and has broad clinical application value. Nevertheless, the mechanism of BMP9 promotes osteogenic differentiation remain unclear. TAZ, a transcriptional co-activator, has great effects on cell proliferation, differentiation, and stem cell self-renewal. In this research, we investigated the effects of TAZ in BMP9-induced osteogenic differentiation of mesenchymal stem cell line C3H10T1/2 (MSCs) and murine multi-lineage cell lines C2C12 and MEFs (MMCs) and explored its possible mechanisms. This study has found that BMP9 induces the expression of TAZ and promotes its nuclear translocation. Meanwhile, our study found that Ad-TAZ and TM-25659, a TAZ agonist, can enhance the osteogenic differentiation of MSCs and MMCs induced by BMP9. Conversely, Ad-si-TAZ and verteporfin, an inhibitor of TAZ, have the contradictory effect. Likewise, the promotion of TAZ to the BMP9-induced ectopic bone formation in vivo was confirmed by the subcutaneous transplantation of MSCs in nude mice. Furthermore, we have detected that TAZ might increase the levels of the phosphorylation of Smad1/5/8, p38, ERK1/2, and JNK induced by BMP9. Additionally, we also found that TAZ increased the total protein level of β-catenin induced by BMP9. In summary, our results strongly indicated that TAZ will promote the osteogenic differentiation in MSCs and MMCs induced by BMP9 through multiple signal pathways.